Evaluating Civics and Religious Education: Foundations for Enhancing Students' National Intelligence - Fatimah Sialana; Susi Anita Patmawati; Titus Gaite; Marlyen Sharly Sapulette; Paisal Ansiska (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to evaluate the effectiveness of integrating Civics Education and Religious Education materials in enhancing students' understanding of citizenship concepts and moral values. The study involves detailing the number of students and the demographic information of two groups of 10th-grade students from three well-accredited high schools in Ambon City, with each group consisting of 35 students: one experimental group and one control group. Data were collected through pre-tests and post-tests, classroom observations, and questionnaires. The research results indicate that the experimental group experienced an increase in average scores from 60 to 85, while the control group only increased from 60 to 70. Paired t-test analyses showed that this increase was statistically significant, with t-values of 3.34 for the experimental group and 2.10 for the control group, both groups having a significance level smaller than 0.05. Observations and questionnaires also revealed that students in the experimental group were more active in classroom discussions and exhibited a more positive attitude toward the material taught. These findings affirm that the integration of civics and Religious Education materials can significantly enhance students' understanding, attitudes, and behaviors regarding moral values and citizenship. This research underscores the significant impact of integrating Civics and Religious Education on enhancing students' understanding of citizenship and moral values. It contributes to the existing literature by providing empirical evidence and emphasizing the necessity of comprehensive teacher training to effectively implement holistic curricula. The implications of this study highlight the need for adequate teacher preparation and ongoing evaluation to ensure successful curriculum integration, positioning this approach as an effective strategy in moral education to shape a younger generation with integrity and responsibility.